2022
DOI: 10.1002/essoar.10511764.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convective impact on the global lower stratospheric water vapor budget

Abstract: Water vapor is an important greenhouse gas and exerts significant influence on the chemistry and radiative balance of the atmosphere (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…"Natural experiments" of injections of INP have already been evaluated: Ueyama et al (13) showed that ice crystals (which act as efficient INP) "injected" into the TTL from the anvils of large convective events generate a net dehydration of the air, even as they themselves represent injections of water. Laboratory experiments also support the intervention concept (14).…”
Section: Introductionmentioning
confidence: 99%
“…"Natural experiments" of injections of INP have already been evaluated: Ueyama et al (13) showed that ice crystals (which act as efficient INP) "injected" into the TTL from the anvils of large convective events generate a net dehydration of the air, even as they themselves represent injections of water. Laboratory experiments also support the intervention concept (14).…”
Section: Introductionmentioning
confidence: 99%
“…To study the effects of tropical waves on QBO and cirrus clouds, global reanalyses provided by different centers for numerical weather prediction have been widely used (Garcia & Richter, 2019; Anstey et al., 2022; Y.‐H. Kim & Chun, 2015; Pahlavan, Fu, et al., 2021; Pahlavan, Wallace, et al., 2021; Ueyama et al., 2023). Due to its higher horizontal resolution compared to its predecessors, the fifth generation European Centre for Medium‐Range Weather Forecasts (ECMWF) Reanalysis (ERA5) is capable to resolve a wider spectrum of tropical waves.…”
Section: Introductionmentioning
confidence: 99%
“…Existing estimates of the contribution of tropopause‐overshooting convection to the LS H 2 O budget are based on observations of storms coupled with trajectory calculations driven by large‐scale winds or on output from convection‐resolving model simulations and vary from 10%–15% globally to 30%–45% regionally (e.g., Dauhut & Hohenegger, 2022; Dessler & Sherwood, 2004; Hanisco et al., 2007; Tinney & Homeyer, 2021; Ueyama et al., 2023). Most existing efforts to compute global LS H 2 O budgets consider only the effects from tropical convection, but it is increasingly recognized that midlatitude overshooting convection is both deep and frequent (S. M. Khaykin et al., 2022; Liu & Liu, 2016; Liu et al., 2020; Werner et al., 2020).…”
Section: Introductionmentioning
confidence: 99%